PENGEMBANGAN DAN UJI AKSEPTABILITAS FORMULA “BELIWUH” PLESTER DEMAM HIDROGEL GUNA ULANG BERBAHAN TANAMAN BELIMBING WULUH (Averrhoa Bilimbi L.) - Sugiharta, Sudrajat; Mudrikah, Siti; Mursal, Iin Lidia Putama; Rahma, Suci; Nisa, Shabrina Zahratun; Zahro, Putri Latifah Nur; Hermawan, Ghifari Hanif (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2025)
Fever is commonly managed using conventional oral medications, however, compresses remain a widely preferred adjunctive therapy. Most commercially available compresses are single-use, making them economically inefficient. Averrhoa bilimbi L. (bilimbi) possesses known antipyretic activity and contains bioactive compounds such as alkaloids, flavonoids, and saponins, which have potential as natural antipyretic agents. This study aimed to develop an optimal formulation based on varying concentrations of PVP K-30 and potassium chloride (KCl), and to evaluate the quality of bilimbi-based hydrogel and hydrogel plaster formulations that are reusable, stable, comfortable to use, and have minimal side effects. An experimental design was employed to prepare three hydrogel plaster formulations using different concentrations of PVP K-30 and KCl. The formulations were evaluated for organoleptic properties, homogeneity, adhesiveness, pH, gel fraction, swelling index, viscosity, thickness, moisture absorption, folding endurance, weight uniformity, and acceptability. All formulations met established quality standards for hydrogel and hydrogel plasters. The resulting plasters exhibited a solid gel consistency, green coloration, and a distinctive green tea scent, with safe pH values ranging from 4.2 to 6.5. The P4K2.5 formulation demonstrated the most stable viscosity (16,575.3 cP), while P4.5K3.5 was identified as the most optimal overall. P3.5K1 was most preferred in terms of color; P4K2.5 and P4.5K3.5 in aroma; and P3.5K1 and P4.5K3.5 in texture. After five hours of use, participants strongly favored P4K2.5 and P4.5K3.5. Notably, P4.5K3.5 also provided the highest cooling sensation after refrigeration and is recommended as a promising candidate for a reusable hydrogel plaster formulation for fever therapy.